Herança genética e potencial de armazenamento de sementes de híbridos de milho - Capelaro, Ademir Luiz (2014)
The present study aimed to evaluate the effects of genetic inheritance in the physiological quality and the storage potential of some corn hybrids seeds produced in the field and stored in two different environments: cold room and common warehouse, for a period of eighteen months. To this study were produced seeds from six corn hybrids by crossing a group of three male parental lines with two female parental lines. Seeds from these hybrids were produced in the Syngenta Production Research field area, located at Tupaciguara-MG, under a high technology environment/condition with a necessary isolation in order to prevent any kind of contamination between their parents. Harvest was done in spikes and after drying and processing, 10 kg of seeds samples each hybrid and parent lines corresponding to 20R size were separated. Then these samples were divided in two sub-samples of 5 kg each one and storage in two different environments: cold room at 10 º C and 60 % RH and common warehouse in natural enviroment (25 - 35° C and 30 - 90% RH). Seeds quality for the two environment conditions was evaluated by using the germination test, acelerating aging test (EVA) and cold test, for a period of eighteen months. The statistical design was completely randomized factorial 3x5 for each hybrid and male and female parent, in five evaluation periods, performed separately for each storage condition, with four replications in case of germination and three replications for each treatment in case of accelerated aging test and cold test. According the results was possible to conclude that the physiological quality of the seeds and their longevity (shelf life) was similar for all hybrids, independent of the different combination of their respective male and female. Also the hybrids have ever presented better performance of their respective parental lines. In all situations evaluated was observed that the hybrids presented higher performance to physiological quality than their respective parent lines, indicating that the effects of the heterosis was very important.